2020
DOI: 10.1177/0022042620961358
|View full text |Cite
|
Sign up to set email alerts
|

Medicate to Graduate: Academic Strain and Nonmedical Prescription Stimulant Use Among Graduate and Undergraduate Students

Abstract: The nonmedical use of prescription stimulants has been prevalent on college campuses in recent years. Previously, nonmedical prescription stimulant use (NMPSU) has been associated with increased use of other illicit substances, drug abuse, school dropout, and arrest. It is, therefore, imperative to understand the etiology of NMPSU for prevention, intervention, and harm reduction purposes. This study builds upon previous research on the role of academic strain in NMPSU by (a) considering a measure of strain tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
(145 reference statements)
0
2
1
Order By: Relevance
“… 43 Recent results from a US-based dataset of 1121 undergraduate and graduate students indicated that the latter are twice as likely to report nonmedical prescription stimulant use than undergraduate students. 63 However, the present study did not find a significant association between the number of years spent at the university and reported PCE substance use. Summing to preuniversity usage, the usage pattern thus seems to remain individually stable, also influenced by the lower societal acceptance and stigmatization of using psychoactive substances.…”
Section: Discussioncontrasting
confidence: 91%
“… 43 Recent results from a US-based dataset of 1121 undergraduate and graduate students indicated that the latter are twice as likely to report nonmedical prescription stimulant use than undergraduate students. 63 However, the present study did not find a significant association between the number of years spent at the university and reported PCE substance use. Summing to preuniversity usage, the usage pattern thus seems to remain individually stable, also influenced by the lower societal acceptance and stigmatization of using psychoactive substances.…”
Section: Discussioncontrasting
confidence: 91%
“…Sleep is de ned as: "a state of immobility that consists of greatly diminished physical responsiveness that allows for reorganization of neural activity [49]" while, sleep deprivation is referred to as "short sleep duration with poor sleep quality [50]". Poor mental health, heart diseases, drug usage, aggressive behavior, and body overweight are commonly known adverse health effects of sleep deprivation [51].…”
Section: Sleep Deprivationmentioning
confidence: 99%
“…Prescription drugs are an indispensable resource for curing illnesses and injuries and for the relief of chronic symptoms. However, there is also a growing demand for the nonmedical use of such drugs, for example, to get high, lose weight, or increase cognitive performance (Faraone et al, 2020; Fuermaier et al, 2021; Hurst, Eassey, Baldwin, & Ten Bensel, 2021; Maier, Ferris, & Winstock, 2018; Teter, DiRaimo, West, Schepis, & McCabe, 2020). Next to buying these drugs on illegal markets, users try to obtain medications by feigning symptoms to get a prescription.…”
Section: Introductionmentioning
confidence: 99%